Organic Matter Stocks and the Interactions of Humic Substances with Metals in Araucaria Moist Forest Soil with Humic and Histic Horizons - Hanke,Daniel (2017)
ABSTRACT Soils with humic and histic horizons in tropical and subtropical ecosystems play an important role in determining the atmospheric C stock and its stabilization, climate regulation, water holding capacity, and environmental filtering, due to the different functions of soil organic matter (SOM). However, the processes and mechanisms that regulate SOM dynamics in these soils are not clear. The objectives of this study were: i) determine the C and N stocks and ii) investigate the SOM chemical fractions and their interactions with Fe and Al ions in soils with humic and histic horizons of a toposequence under Araucaria moist forest in southern Brazil. The soils sampled were classified as Humic Hapludox (top - not hydromorphic), Fluvaquentic Humaquepts (lower third - hydromorphic), and Typic Haplosaprists (floodplain - hydromorphic). The C and N contents were determined in bulk soil samples and SOM chemical fractions; in these fractions, Fe and Al co-extracted contents were also determined. The chemical composition of humin and humic acid fractions was investigated by FTIR spectroscopy. The C content in the toposequence increased from the top to the lowest position. The differences observed in SOM content and SOM chemical composition were defined by the differences in soil water regime. The amount of C stored in the subsurface horizons is about 70 % of total organic C. The carbohydrate-like structures in the humin fraction were protected from solubilization through interaction with iron oxides, which may represent an important mechanism for labile organic compound preservation in these soils. The soluble humic substances showed the highest Fe and Al contents, and their compartments have different affinities for Fe and Al.